A Low-cost Environmental Control System for Precise Radial Velocity Spectrometers. (1st November 2017) - Sliski, David H.; Blake, Cullen H.; Halverson, Samuel
Abstract: We present an environmental control system (ECS) designed to achieve milliKelvin (mK) level temperature stability for small-scale astronomical instruments. This ECS is inexpensive and is primarily built from commercially available components. The primary application for our ECS is the high-precision Doppler spectrometer MINERVA-Red, where the thermal variations of the optical components within the instrument represent a major source of systematic error. We demonstrate ±2 mK temperature stability within a 0.5 m 3 thermal enclosure using resistive heaters in conjunction with a commercially available PID controller and off-the-shelf thermal sensors. The enclosure is maintained above ambient temperature, enabling rapid cooling through heat dissipation into the surrounding environment. We demonstrate peak-to-valley (PV) temperature stability of better than 5 mK within the MINERVA-Red vacuum chamber, which is located inside the thermal enclosure, despite large temperature swings in the ambient laboratory environment. During periods of stable laboratory conditions, the PV variations within the vacuum chamber are less than 3 mK. This temperature stability is comparable to the best stability demonstrated for Doppler spectrometers currently achieving m s −1 radial velocity precision. We discuss the challenges of using commercially available thermoelectrically cooled CCD cameras in a temperature-stabilized environment, and demonstrate that the effects of variable heat output from the CCD camera body can be mitigated using PID-controlled chilled water systems. The ECS presented here could potentially provide the stable operating environment required for future compact "astrophotonic" precise radial velocity (PRV) spectrometers to achieve high Doppler measurement precision with a modest budget.